Implementation of Land Acquisition for Public Interest on Uncertified Land (Case Study of Kebumen Police Station Development in 2024) - Robby Nur Hikmah, (Semarang State University Undergraduate Law and Society Review, 2025)
The difference in compensation value for land acquisition for public interest between certified and uncertified land can be seen in the case of land acquisition for the Kebumen Police in 2024. Existing legal provisions do not clearly differentiate the compensation value based on proof of ownership, thus creating legal uncertainty. This study aims to determine the legal certainty for owners of uncertified land and the implementation of the land acquisition. The method used is a qualitative approach with an empirical legal research type, through interviews, observations, and document studies. The results of the study show that uncertified land can be assessed using non-certificate documents, and the assessment is carried out with reference to the Indonesian Assessment Standards (SPI) 204. This study recommends accelerating community land registration in order to reduce disparities in compensation values, as well as the need for stricter regulations regarding the standards for proving ownership of uncertified land. In addition, SPI 204 needs to be explicitly included in laws and regulations or become an attachment to the technical regulations for implementing land acquisition in order to have clearer and more binding legal force.